2009
DOI: 10.1105/tpc.109.066167
|View full text |Cite
|
Sign up to set email alerts
|

Transcript-Based Cloning ofRRP46, a Regulator of rRNA Processing andRGene–Independent Cell Death in Barley–Powdery Mildew Interactions  

Abstract: Programmed cell death (PCD) plays a pivotal role in plant development and defense. To investigate the interaction between PCD and R gene-mediated defense, we used the 22K Barley1 GeneChip to compare and contrast time-course expression profiles of Blumeria graminis f. sp hordei (Bgh) challenged barley (Hordeum vulgare) cultivar C.I. 16151 (harboring the Mla6 powdery mildew resistance allele) and its fast neutron-derived Bgh-induced tip cell death1 mutant, bcd1. Mixed linear model analysis identified genes assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 68 publications
1
22
0
Order By: Relevance
“…Interestingly, about 300 transcripts accumulated either only in the RRP4-depleted or only in the RRP41-depleted sample. This confirmed that individual subunits of the core complex affect specific substrates and have different contributions to the in vivo activity of the exosome, as has already been suggested by the distinct phenotype of the mutants (Chekanova et al 2007;Hooker et al 2007;Xi et al 2009). However, about 500 transcripts were upregulated in both samples and likely represent the common substrates of the exosome core complex (Chekanova et al 2007).…”
Section: Polyadenylation-assisted Rna Degradation By the Nuclear Exosomesupporting
confidence: 83%
See 1 more Smart Citation
“…Interestingly, about 300 transcripts accumulated either only in the RRP4-depleted or only in the RRP41-depleted sample. This confirmed that individual subunits of the core complex affect specific substrates and have different contributions to the in vivo activity of the exosome, as has already been suggested by the distinct phenotype of the mutants (Chekanova et al 2007;Hooker et al 2007;Xi et al 2009). However, about 500 transcripts were upregulated in both samples and likely represent the common substrates of the exosome core complex (Chekanova et al 2007).…”
Section: Polyadenylation-assisted Rna Degradation By the Nuclear Exosomesupporting
confidence: 83%
“…In plants, the situation appears to be different, and more complex: First, in contrast to yeast and human exosomes, the plant core subunit AtRRP41 has a phosphorolytic activity that is stimulated by short poly(A) tails, at least in vitro (Chekanova et al 2000). Second, downregulation of individual subunits of the plant core exosome results in differential plant phenotypes (Chekanova et al 2007;Hooker et al 2007;Xi et al 2009). Moreover, downregulation of the core subunits AtRRP41, AtRRP4, or AtCSL4 resulted in accumulation of different polyadenylated RNAs, indicating that each of the proteins functions in polyadenylation-assisted RNA decay, albeit affects a distinct set of substrates (Chekanova et al 2007).…”
Section: Polyadenylation-stimulated Exoribonucleasesmentioning
confidence: 99%
“…Likewise transcriptional patterns of homologous genes and a similar neighbourhood in co-expression networks in different species might also support the identification of gene orthologs in different species (Mutwil et al, 2008;Schreiber et al, 2009). Furthermore, micro-array analyses proved effective in transcript-based cloning in barley forward genetic approaches (Xi et al, 2009;Zhang et al, 2009).…”
Section: Introductionmentioning
confidence: 90%
“…Additionally, it has been suggested that the plant exosome displays an even higher degree of structural and functional flexibility as particular subunits seem to be dispensable for viability and processing of certain subsets of substrates. 31,43 This is in contrast to the S. cerevisiae exosome, where all Exo-9 subunits are essential for viability, 20 but reminiscent of data from D. melanogaster that suggest the presence of various subcomplexes consisting only of a subset of the Exo-9 subunits and co-factors. 25,32,44 This situation is quite unexpected from evolutionary and structural viewpoints and thus requires further experimental validation.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 98%